Upaya Pengelolaan Limbah Produksi Etanol Melalui Rencana Pembangunan IPAL di Desa Ngombakan, Kecamatan Polokarto, Kabupaten Sukoharjo - Zakaria, Salsabila Anggraini; Sumartiningsih, Sri; S, Sumidi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study examines the legal framework and local efforts for managing ethanol production waste in Ngombakan Village, Polokarto District, Sukoharjo Regency. The analysis employs a normative juridical approach supported by empirical data gathered from interviews with village officials. The legal review shows that ethanol waste management is bound by environmental protection norms, effluent quality standards, risk-based business licensing, and village authority in environmental stewardship. Empirical findings indicate that the village government has planned the construction of a communal wastewater treatment facility (IPAL) to address pollution, yet faces challenges related to land availability and funding. The study concludes that stronger regulatory support, technical assistance, and community participation are essential to achieving sustainable ethanol waste management.